Open-Ended Learning Model Effect on Critical and Creative Thinking in Islamic Education - Khotib Raja Ritonga; Andi Murniati; Djefrin E. Hulawa (Yayasan Letiges Konsultan Sosial, 2026)
This study aims to examine the effect of the Open-Ended Learning model on students' critical and creative thinking skills in Islamic Religious Education learning at SMP Negeri 8 Pekanbaru. The study is motivated by the gap between theoretical demands for developing higher-order thinking skills that require complex prerequisites and the reality of limited educational resources, as well as the urgency of contributing to achieving SDG 4 on quality education. The research employs a quantitative, quasi-experimental, nonequivalent control-group design, involving 70 students divided into an experimental class (34 students) and a control class (36 students). Data were collected using validated critical and creative thinking skills test instruments, then analysed using the Independent Samples t-tests and MANOVA. The results show significant differences between the experimental and control classes, with the experimental class achieving a critical thinking posttest average of 79.12 compared to 70.14 (sig. 0.001), and a creative thinking posttest average of 81.76 compared to 74.58 (sig. 0.010). Multivariate tests confirm a significant simultaneous effect (Wilks' Lambda F=8.642, sig. 0.000), proving that the Open-Ended Learning model effectively develops both skills in an integrated manner. These findings demonstrate that open-ended problem-based learning can transform the paradigm of Islamic Religious Education from doctrinal transmission to intellectual exploration, producing a generation of Muslims capable of thinking critically, creatively, and contextually in applying Islamic values, while significantly contributing to the SDGs agenda through the formation of essential 21st-century competencies for sustainable development.